Cardiovascular risk in infants overweight and obese - Pajuelo R., Jaime (2013)
Overweight and obesity lead the occurrence of comorbidities such as type 2 diabetes mellitus, hypertension, anddyslipidemias. Objectives: To determine the presence of cardiovascular risk in children and adolescents overweight and obese,by gender and age groups. Design: Cross sectional study. Participants: Children and adolescents of both genders, 5-18 year-old.Interventions: Diagnosis of overweight and obesity was done according to Must et al. classification with the following criteria: 85 to 95for overweight and more than 95 percentile for obesity. Serum lipid profile, glucose and insulin were analyzed, and with the latter twoHOMA index was determined to identify insulin resistance (IR), using Matthew´s equation, the metabolic syndrome (MS) with referenceto Cook and dyslipidemias (D) with Friedman and Daniels’ suggestions. Main outcome measures: Cardiovascular risk. Results: Obesechildren had higher cardiovascular risks than overweight: IR 77.8%, SM 22.2%, D: total cholesterol (TC) 64.4%, HDL-C 33.3%, LDL-C19.5% and triglycerides (Tg) 40%. Males had higher risk than females regardless of nutritional status: IR 74.1%, SM 22.2%, D: TC63%, HDL-C 37%, LDL-C 36%, Tg 40.7%. Children over 10 had IR 78% and HDL-C 31.7%; other risk factors were higher in thoseunder 10 years. Conclusions: Risks affected obese more than overweight children, more to males, and those over 10 years had higherprevalence of IR and low HDL-C. With higher BMI more cardiovascular risk and serious health compromise, worrisome because ofearly age onset.